Mentalization-based Treatment in Groups — a Paradigm Shift or old Wine in New Skin?. (March 2014) - Potthoff, Peter; Moini-Afchari, Ute
Empirical studies demonstrate good efficiency of mentalization-based treatment (MBT) as developed by Fonagy, Bateman and Target in the therapy of borderline personality disorder. The reception of these results shows two opposing positions. One argues that MBT offers a paradigm shift because it is capable of profoundly changing or even replacing group analysis. The other position expresses doubts that MBT offers anything essentially new. The authors of this article reflect on both positions and demonstrate how MBT is generally useful as part of a broadened praxeology of group analysis even extending beyond borderline-pathology. They describe their experience in out-patient groups they have conducted together, and show how typical MBT-interventions fit in with the usual repertoire of group-analysis. Different kinds of interventions are discussed with respect to different degrees of mentalization capacity. Whenever there is a partial lack or suspension of mentalization capacity, interventions in the sense of 'MBT-informed group-analysis' are apt to help get out of an impasse. So there is no alternative between MBT or group-analysis. The author's plea is for MBT to be part of group-analysis.